The vigilance regulation model of affective disorders and ADHD - Hegerl, Ulrich; Hensch, Tilman (Neuroscience and biobehavioral reviews, 2014)
According to the recently proposed vigilance model of affective disorders (vigilance in the sense of "brain arousal"), manic behaviour is partly interpreted as an autoregulatory attempt to stabilise vigilance by creating a stimulating environment, and the sensation avoidance and withdrawal in Major Depressive Disorder (MDD) is seen as an autoregulatory reaction to tonically increased vigilance. Indeed, using a newly developed EEG-based algorithm, hyperstable vigilance was found in MDD, and the contrary, with rapid drops to sleep stages, in mania. Furthermore, destabilising vigilance (e.g. by sleep deprivation) triggers (hypo)mania and improves depression, whereas stabilising vigilance, e.g. by prolonged sleep, improves mania. ADHD and mania have common symptoms, and the unstable vigilance might be a common pathophysiology. There is even evidence that psychostimulants might ameliorate both ADHD and mania. Hyperactivity of the noradrenergic system could explain both the high vigilance level in MDD and, as recently argued, anhedonia and behavioural inhibition. Interestingly, antidepressants and electroconvulsions decrease the firing rate of neurons in the noradrenergic locus coeruleus, whereas many antimanic drugs have opposite effects.